Notch1 modulates mesenchymal stem cells mediated regulatory T‐cell induction. Issue 1 (5th December 2012) - Del Papa, Beatrice; Sportoletti, Paolo; Cecchini, Debora; Rosati, Emanuela; Balucani, Chiara; Baldoni, Stefano; Fettucciari, Katia; Marconi, Pierfrancesco; Martelli, Massimo F.; Falzetti, Franca; Di Ianni, Mauro
<x xml:space="preserve">Abstract</x> Notch1 signaling is involved in regulatory T (Treg)‐cell differentiation. We previously demonstrated that, when cocultured with CD3+ cells, mesenchymal stem cells (MSCs) induced a T‐cell population with a regulatory phenotype. Here, we investigated the molecular mechanism underlying MSC induction of human Treg cells. We show that the Notch1 pathway is activated in CD4+ T cells cocultured with MSCs. Inhibition of Notch1 signaling through GSI‐I or the Notch1 neutralizing antibody reduced expression of HES1 (the Notch1 downstream target) and the percentage of MSC‐induced CD4+CD25highFOXP3+ cells in vitro. Moreover, we demonstrate that FOXP3 is a downstream target of Notch signaling in human cells. No crosstalk between Notch1 and TGF‐β signaling pathways was observed in our experimental system. Together, these findings indicate that activation of the Notch1 pathway is a novel mechanism in the human Treg‐cell induction mediated by MSCs.